Upaya Proaktif Guru PAK dalam Mengatasi Pengaruh Negatif Fear of Missing Out pada Kesehatan Mental Remaja - Morgan Ndaha Nggongu; Cristian Seldjatem (Jurnal Budi Pekerti Agama Kristen dan Katolik, 2024)
The Fear of Missing Out (FoMO) phenomenon that is increasingly prevalent in the digital age has a significant impact on the mental health of adolescents, including among Christian teenagers. FoMO is characterized by feelings of anxiety due to fear of being left behind from other people's activities or achievements, often triggered by social media. This study aims to identify proactive efforts that Christian Religious Education (PAK) teachers can make in overcoming the negative influence of FoMO on adolescent mental health. The method used is a qualitative study with a descriptive approach, through in-depth interviews and observations of PAK teachers and adolescents in a Christian education environment. This study also used a literature review to strengthen the understanding of the role of PAK teachers in the spiritual and social context. The results show that PAK teachers have a crucial role in guiding adolescents to understand their spiritual identity, teaching the wise use of technology, and creating a learning environment that supports mental health. PAK teachers can also be role models who motivate adolescents to focus on a personal relationship with God and not get caught up in social comparisons. With these efforts, it is hoped that adolescents can overcome FoMO pressure and develop better mental health.